Application of the Health Literacy INDEX on the development of a manual for prevention of falls for older adults. Issue 1 (January 2017) - Andrade, Isabel; Silva, Catarina; Martins, Anabela Correia
Highlights: Most health information materials are not customized for patient' readability level. Use of INDEX checklist improved the development of the manual for falls prevention. Peer engagement is central for obtaining an age-friendly manual for falls prevention. Abstract: Objective: The Health Literacy INDEX tool has been developed for creating accessible and readable health information materials for people of all literacy levels. To increase knowledge of falls risk factors and actively engage older adults, we developed an improved manual for prevention of falls for low-health literacy older people entitled "Preventing falls-I can do it", with the aid of INDEX. Methods: First time application of the INDEX tool for assessing the health literacy demands of available manuals for prevention of falls for older adults and subsequent development of an improved manual using the INDEX tool as a checklist, supported by a pretest phase involving sixteen adults ≥65, living in the community, with literacy ≤4th grade and limited functional health literacy. Results: The engagement of older adults from the target audience and their feedback obtained during the validation process contributed to the development of an improved health literacy- and age-friendly manual for prevention of falls. Conclusion: By offering effective health information materials, older adults can play a more active role in their health care. Practice implications: The manual developed to be health literacy- and age-friendly is available to be included in any multifactorial program for the prevention of falls in older adults.